Circulating tumor DNA status and dynamics predict recurrence in patients with resected extrahepatic cholangiocarcinoma - Yoo, Changhoon; Jeong, Hyehyun; Jeong, Jae Ho; Kim, Kyu-pyo; Lee, Seonmin; Ryoo, Baek-Yeol; Hwang, Dae Wook; Lee, Jae Hoon; Moon, Deog-Bog; Kim, Ki-Hun; Lee, Sang Soo; Song, Tae Jun; et al. (Journal of hepatology, 2025)
Surgery is the only curative therapeutic option for resectable extrahepatic cholangiocarcinoma, but recurrence is common, and prognosis is poor. There is an unmet clinical need for improved decision-making regarding adjuvant chemotherapy (ACT). Herein, we evaluated the usefulness of monitoring longitudinal circulating tumor DNA (ctDNA) for molecular residual disease (MRD) in patients from the STAMP trial, which compared the efficacy of adjuvant capecitabine (CAP) vs. gemcitabine plus cisplatin (GemCis). Between July 2017 and November 2020, 101 patients were randomized 1:1 to receive GemCis (n = 50) or CAP (n = 51). Efficacy outcomes were analyzed with an extended follow-up of 19 months from the previous report. From a biomarker cohort of 89 patients, longitudinal plasma samples (n = 254) were prospectively collected post-surgery before ACT, and on-ACT at 12 and 24 weeks from cycle 1 day 1 (C1D1). ctDNA was evaluated using a personalized, tumor-informed, 16-plex PCR next-generation sequencing assay and was correlated with clinical outcomes. In the extended follow-up analysis, median disease-free survival (DFS) and overall survival did not significantly differ between the CAP and GemCis groups. Significantly inferior DFS was associated with ctDNA positivity before ACT (hazard ratio [HR] 1.8; p = 0.029), on-ACT at 12 weeks from C1D1 (HR 7.72; p <0.001), on-ACT at 24 weeks from C1D1 (HR 5.24; p <0.001), and anytime post-surgery (HR 3.81; p <0.001). Analysis of pre-treatment to on-treatment ctDNA dynamics revealed that serially ctDNA-negative patients exhibited a significantly longer DFS compared to those with sustained ctDNA positivity (HR 6.7; p <0.001) or those who turned ctDNA positive (HR 5.8; p <0.001). In patients with resected extrahepatic cholangiocarcinoma, ctDNA status and dynamics predicted recurrence during adjuvant therapy, and may help optimize clinical decision-making. The findings from this study highlight the critical role of ctDNA as a prognostic biomarker and monitoring tool for patients with resected extrahepatic cholangiocarcinoma. By demonstrating the superiority of ctDNA to predict disease recurrence compared to conventional biomarkers such as cancer antigen 19-9 and carcinoembryonic antigen, this study underscores its potential in guiding decision-making during adjuvant chemotherapy. These results may be crucial to refine post-surgical treatment strategies and improve patient outcomes. The practical application of ctDNA monitoring could lead to more personalized treatment approaches, enabling timely interventions based on molecular residual disease status. NCT03079427. [Display omitted] •No DFS or OS difference between adjuvant CAP and GemCis in resected LN+ eCCA.•Tumor-informed ctDNA status predicts recurrence in patients with resected eCCA.•ctDNA status outperforms CA 19-9 and CEA in predicting survival outcomes.•Personalized ctDNA monitoring helps optimize adjuvant therapy decision-making.